The Strategy of the Principal in Improving Teacher Competence - Fitriah, Fitriah (Yayasan Sembilan Pemuda Indonesia, 2023)
Teachers have a vital role in the educational process. Teacher competence could determine the realization of a quality learning process. This study aimed to describe the principal’s strategy to improve teacher competence. The type of research was descriptive-qualitative research. Data collection tools included documentation, interviews, observation, and literature reviews. Data analysis techniques used descriptive and qualitative analysis techniques. The results of the study stated that the school principal’s strategy to increase teacher competence through needs analysis, preparation of program plans, implementation, and evaluation of the implementation of increasing teacher competence had gone well and had a positive impact on increasing teacher competence. Increased teacher competence through the implementation of the principal’s strategic program has an impact on the quality of learning in SMA Negeri 3 Kayuagung. personality aspects are carried out by providing motivation and good examples for teachers to always do the best for students and the progress of the institution.